Transdisciplinary Approach in Palliative Care MDT Meetings – A Way Forward - Annum Ishtiaq (Journal of Liaquat National Hospital, 2024)
Palliative care stands as an imminent and evolving facet of medicine, specifically tailored for individuals grappling with complex cancer or terminal illnesses. Its primary goal is to enhance the quality of life for both patients and their families by mitigating suffering through early identification, accurate assessment, and treatment of symptoms [1]. This specialized care adopts a transdisciplinary team approach, addressing the physical, psychological, social, and spiritual needs of patients. This collaborative team comprises physicians, nurses, various ancillary home-health care teams, and chaplains [2]. The palliative care team serves as an exemplar of health professional development and teamwork, offering a platform to empower ancillary team members for active participation in patient care [3]. Multidisciplinary team (MDT) meetings serve as pivotal platforms where a consortium of healthcare professionals convene to strategize and design optimal diagnostic and therapeutic treatment pathways for patients with intricate needs [4]. These meetings yield evidence-based care plans developed by a diverse group of specialists, minimizing variations in practice patterns, and efficiently utilizing healthcare resources. The outcome of MDT meetings is time-efficient, cost-effective, and quality care that enhances patient satisfaction [4]. In Palliative Care MDT serves as a meaningful platform for physicians and allied healthcare staff to share ideas and voice their opinions. Navigating the care of a patient in the terminal phase or nearing the end of life is always intricate. It necessitates the recognition and addressing of psychosocial, spiritual, and emotional distress alongside physical pain and agony [1, 3]. The collective efforts of a team are commendable, reflecting the diversity within the group and fostering innovative ideas that best suit the needs of patients and their families [5]. Within a Palliative MDT, group discussions encompass a spectrum of expertise. Say for example A wound-care nurse may evaluate decubitus ulcers and propose practical and cost-effective interventions. Pharmacists contribute ideas for formulating rescue medications, especially during crises when intravenous or subcutaneous routes are inaccessible. Nutritionists devise diet plans to counter malignancy-related cachexia and alleviate the side effects of opioid analgesics while meeting adequate calorie requirements. The involvement of the home health care team is critical, as implementing these recommendations for home-based palliative care patients is challenging and demands strong and effective communication. A psychologist addresses the caregiver’s stress and the patient’s recognition of nearing death. These diverse contributions are indispensable in providing high-quality care within the current healthcare delivery system in the country. Interestingly, it is not paternalistic or physiciancentred and the palliative care physician is cognizant and inclusive of other stakeholders, this indeed creates a positive and productive workforce. The collaborative efforts by the palliative team for terminally ill patients can be a model that has the potential to ease the strain on a fragmented and crumbled healthcare system in a low-middle-income country such as Pakistan. Working together as a team, and acknowledging each other’s expertise is crucial [6]. With the changing landscape of medicine and advancement in healthcare, it is imminent to recognize and acknowledge the ancillary healthcare professionals and their contributions [6, 7].